The Psychological Analysis of Divorce at Early Marriage - Zadrian Ardi; Nining Maizura (Universitas Negeri Padang, 2018)
Marriage purposes are to form a prosperous and happy family forever. Happy the family is a reflection of the harmony of a family. But in the last few years many phenomena are emerging about the problems in the family that makes the family becomes unharmonious such as quarrels, jealousy, infidelity, income differences, and differences in life principles and to the action to end marriage or divorce. Households are very dangerous if they keep on continuing though in the family difference is a reasonable thing. Problems that occur should immediately find the best solution so as not to cause negative impacts for the family. Solving various problems in the family one of them can be completed through counseling so that the problems faced can be resolved. This study aims to get a picture of the psychological impact of divorce at the beginning of marriage. The research method used in this research is qualitative research. In this study, the variables that will be examined the psychological impact on divorce early in the marriage will be explored in depth.